Hubungan Tingkat Konsentrasi Siswa Dengan Shooting Undering Dalam Permainan Bola Basket Ekstrakurikuler Sekolah Menengah Pertama - Helmy Nurhidayah; Andrie Chaerul; Febi Kurniawan (Jurnal Ilmiah Wahana Pendidikan, 2022)
In the game of basketball one of the components that is needed is concentration. Concentration is very important in both the posture for jumping and passing along the field, especially when shooting, concentration is something that must be considered because it can affect the entry of the ball into the basketball hoop. In this era of the year, basketball is very popular with people from among teenagers and parents. Basketball is also a sports achievement in the world of education. In the game of basketball there is a shooting technique which is how to throw the ball from under the ring or it can be called shooting undering. Each activity we require concentration in order to do well. Concentration is also needed in the world of sports, such as throwing, kicking or shooting so that it can be released properly. In this study, 20 samples were used, consisting of 7 women and 13 men who were taken by purposive sampling technique. The type of research used is non-experimental with a correlational approach. The instruments used were a grid concentration test questionnaire and a 30 second shooting undering test. This data was carried out on extracurricular basketball extracurricular participants at SMP Negeri 1 Tambelang. Based on the data that has been discussed, rcount is smaller than rtable (0.008<0.444) with a significance of 0.574>0.05 where Ho is accepted and Ha is rejected, which means there is no relationship in the study of concentration levels and undershooting at SMP Negeri 1 Tambelang. Keywords : Student concentration, Basketball extracurricular, Grid Conference Questionnaire